Analysis of the special features of the thermal process in an induction generator at high saturation of the magnetic system - Chenchevoi, V.; Romashykhin, Iu; Romashykhina, Zh.; Al-Mashakbeh, Atef S. (Електротехніка і електромеханіка, 2017)
Purpose. Development of the method for the assessment of the thermal operation modes of an autonomous electrical power system with an induction motor, aiming at improvement of the reliability of electricity supply and the quality of electric energy.
Methodology. Induction generator mathematical modeling taking into account the magnetic system saturation was used in the
research. A heat model taking into account the excess of the temperature of the induction generator units in the mode of high
saturation was developed. The obtained results were compared with the experimental data. Results. The paper contains the solution to the problem of improvement of the mathematical model sand methods for steel losses determination in there search of the
operation modes of an autonomous uncontrolled induction generator taking into consideration the properties of the magnetic
system in the mode of high saturation. The expression for determination of steel losses in the mode of high saturation is obtained.
It enables the assessment of the induction generator thermal condition. Originality. The analytical dependence for the calculation
of the steel losses in the mode of magnetic system saturation has been obtained for the first time. Practical value. The obtained
expression for the calculation of the steel losses can be used for determination of the admissible time of generator operation at
overload. It will allow avoiding broken winding insulation and complete use of the generator overload capacity. As a result, it will
reduce possible irregularities of electricity supply due to the generator preliminary cutoff Цель. Разработка методики оценки тепловых режимов работы автономной электроэнергетической системы с асинхронным генератором с целью повышения надежности электроснабжения и качества электроэнергии. Методология. Для проведения исследований использовалось математическое моделирование асинхронного генератора с учетом насыщения магнитной системы. Разработана тепловая модель, которая учитывает превышение температуры узлов асинхронного генератора в режиме высокого насыщения. Полученные результаты моделирования сравнивались с экспериментальными данными. Результаты. В работе решена задача усовершенствования математических моделей и методов определения потерь
в стали при исследовании режимов работы автономного нерегулируемого асинхронного генератора с учетом свойств магнитной системы в режиме высокого насыщения. Получено выражение для определения потерь в стали в режиме высокого
насыщения, которое позволяет оценивать тепловое состояние асинхронного генератора. Оригинальность. Впервые получена аналитическая зависимость для расчета потерь в стали в режиме насыщения магнитной системы. Практическое
значение. Полученное выражение для расчета потерь в стали может быть использовано для определения допустимого
времени работы генератора при перегрузке. Это позволит избежать повреждения изоляции обмоток и в полном объеме
использовать перегрузочную способность генератора. В результате это снизит возможные перебои с электрической энергией из-за преждевременного отключения генератора